Poor Sleep Quality in Critically Ill Patients - Sri Setiyarini; Desy Listyaningrum; Irni Fuzi Wijayanti; Setyo Triatmojo; Hersinta Retno Martani; Yunita Cahyaningsih; Gunawan; Hardi Apriyanto; Endang Suryaningsih; Husna Yulianingsih (Faculty of Nursing, Universitas Hasanuddin, 2026)
Aims: This study aimed to evaluate the sleep quality of critically ill patients in Indonesia. Additional aims are to compare sleep quality among patients using both the Richards-Campbell Sleep Questionnaire (RCSQ) and smartwatch-based data. Methods: A descriptive cross-sectional study was conducted involving adult critically ill patients in three hospitals in Indonesia. A total of 437 patients completed the RCSQ, with 26 of these individuals additionally utilizing a smartwatch to objectively assess sleep quality. A frequency distribution was employed to analyze all samples exhibiting poor quality, alongside the Mann-Whitney test to compare RCSQ and smartwatch scores. Results: Among 437 participants, 217 patients (49.7%) were classified as having poor sleep quality based on a mean (±SD) RCSQ score of 59.26±24.8, below a cut-off point of 63.4. Mean (±SD) scores across RCSQ domains were as follows: the sleep depth (60.87±27.97), sleep latency (56.68±27.99), awakening (56.99±27.10), sleep continuity (59.30±28.28), and sleep quality (59.30±28.28). The measurement results from smartwatch data indicated an overall sleep quality score of 72.42±9.72. No significant difference was observed between the total score of RCSQ and smartwatch sleep quality (p=0.297). Conclusion: Critically ill patients demonstrated generally poor sleep quality, with sleep latency and awakening being the most affected domains